2021
DOI: 10.2106/jbjs.cc.21.00343
|View full text |Cite
|
Sign up to set email alerts
|

A Curious Case of a Wooden Toothpick Inside a Child’s Knee

Abstract: Case: A 10-year-old boy presented with vague symptoms, a few days after a nondescript injury to his left knee. History, examination and blood tests, and imaging were unremarkable. Because of his severe pain, we proceeded to arthroscopy. On proceeding to arthroscopy, a wooden toothpick was found inside the knee joint. The wooden toothpick was removed arthroscopically. Conclusion: The physicians/surgeons have to be vigilant and should approach holisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is common for children and adolescents to lodge foreign bodies into the tissues of their extremities 4 . Agarwal found that more than 80% of patients with retained foreign bodies were boys and 58% involved the foot 5 .…”
Section: Discussionmentioning
confidence: 99%
“…It is common for children and adolescents to lodge foreign bodies into the tissues of their extremities 4 . Agarwal found that more than 80% of patients with retained foreign bodies were boys and 58% involved the foot 5 .…”
Section: Discussionmentioning
confidence: 99%